THE VERTEBRATE FAUNA OF THE LOWER PLIOCENE CONTINENTAL DEPOSITS IN THE EBRO DELTA (BAIX EBRE BASIN, NE SPAIN) (RIVISTA ITALIANA DI PALEONTOLOGIA E STRATIGRAFIA, 2024)
The Pliocene faunas of the northeastern Iberian Peninsula are poorly known due to the scarcity of deposits from this interval. In this context, the site of Sant Nofre-Campredó (Baix Ebre, Catalonia, Spain), comprising two contemporaneous outcrops belonging to geologically correlated sections (Sant Nofre and Campredó-Via Fèrria), makes a significant contribution to the study of Pliocene faunas in this region. The first vertebrate remains were recovered in the late 1970s in clay deposits close to the Sant Nofre Hill. Later, intensive sampling in the 1980s at the Campredó-Via Fèrria outcrop led to the recovery of more than a hundred fossil specimens, including small vertebrates and large mammals. Here, we revise these collections to expand and update the vertebrate list, better constrain the age of the continental deposits, and characterize the environment and climate around the mouth of the Ebro River during the formation of the site. Up to 24 vertebrate species have been identified at Sant Nofre-Campredó, including amphibians, reptiles, and mammals. The presence of the rodents Paraethomys baeticus Piñero & Verzi, 2020, Apocricetus barrierei (Mein & Michaux 1970), and Occitanomys brailloni  Michaux, 1969 implies an early Ruscinian age (MN14 unit) for the two outcrops. Biostratigraphic correlations with other well-dated sites in the Iberian Peninsula refine the estimated age of Sant Nofre-Campredó to approximately 4.6 Ma. The ecological affinities of the identified fauna reveal a landscape dominated by woodland habitats in the surroundings of the site during the Early Pliocene, with presence of open humid meadows and water bodies under warm and moist climatic conditions.
Keywords: Iberian Peninsula; Ruscinian; amphibians; reptiles; mammals; palaeoecology